FEATURES OF PATRIOTIC EDUCATION OF PRIMARY SCHOOL STUDENTS UNDER THE CONDITIONS OF TODAY’S CHALLENGES - Bilavych, Halyna; Ozarko, Veronika; Krainyk, Diana-Mariia; Litvin, Yulia (Mountain School of Ukrainian Carpaty, 2022)
Raising a child as a patriot and citizen has always been at the center attention of state policy in the field of education (The concept of national-patriotic education of children and youth, 2015), theory and practice of Ukrainian education and pedagogical science. This problem is especially relevant under the conditions of Russian-Ukrainian war. In the conditions of challenges that Ukraine has faced, in particular, Ukrainian school, the educational process must be built taking into account the conditions of one of the most brutal wars in modern history: the education of civil patriotism should be based on statesmanlike positions. Today, it is necessary to build a new model of a young patriot. It is worth giving up generally accepted beliefs and build active state-oriented patriotism. Examples of national heroes should be those who gave his life for the freedom of Ukraine, especially in its confrontation with Moscow during more than four hundred years of struggle. Educational process in new Ukrainian school should be based on the approval of Ukrainian statehood idea. Nowadays it is necessary to teach national history at the appropriate level, where priorities should be clearly set, national figures that led to the establishment of statehood ideals, for whom Ukraine was above all else (Ukrainian Cossacks, Legion of Ukrainian Sich Riflemen, Ukrainian Insurgent Army and etc.), actualized. Today's soldiers, who are on the front lines fighting for independence of Ukraine with the Russian aggressor, are those national heroes who are to become an educational ideal for Ukrainian children. It is necessary to remember about commemoration of those who died for the freedom of Ukraine, emphasize the meaning of national liberation struggles in the aspect of the civilizational development of Ukraine throughout its history. It is worth taking into account the pedagogical conditions for the effectiveness of patriotic education of younger students in the educational process of primary school: it is about the systematic work of teachers on the formation of patriotic feelings of education seekers on solid statesmanship positions; impact on consciousness of younger schoolchildren using various means for the formation of patriotic ideas and concepts, the organization of various educational activities; involvement of younger schoolchildren in various forms of practical patriotic activities (volunteering, charity), participation in "adult" patriotic events, the purpose of which is to help the Armed Forces, internally displaced persons, people in the de-occupied territories; the common activities of teachers and families on patriotic education of younger schoolchildren; actualization of the regional component of patriotic education; etc.